Improvement of Student Physics Learning Outcomes through Peer Tutor Learning Model of SMA 3 Bengkalis - Suryani, Suryani (FKIP-Universitas Riau, 2019)
This research was a classroom action research using a peertutor learning model to improve physics learning outcomes. Peer tutorlearning is a learning that utilizes classmates who have more ability tohelp their friends in carrying out an activity or understanding the conceptof learning. The problem to be solved is the low physics learningoutcomes of class XI IPA 3 in SMA 3 Bengkalis. This study consisted ofthree cycles, in each cycle consisting of four stages, namely Planning,Implementation, Observation and Reflection. This research involved 21students which are consisting of 13 female students and 8 male students.In the pre-cycle process, the percentage of learning completeness was19.05%, then after learning the first cycle using the peer tutoring modelthere was an increase in the percentage of learning completeness to42.89%. In the second cycle, it increased again to 61.91% and in the thirdcycle, it succeeded in achieving the percentage of learning completenessof 85.71%. The results showed that an increase in student learningoutcomes along with the application of peer tutoring models. Thus, theresults of the study indicate that the use of peer tutoring models canimprove the physics learning outcomes of XI IPA 3 students in SMA 3Bengkalis.